A review of the role of liver resection in the treatment of human immuno-deficiency virus-positive patients with hepatocellular carcinoma - Coelho, Marcio B.; Teixeira, Uira F.; Waechter, Fabio L.; Fontes, Paulo R. O.; Rodrigues, Pablo D. (International Surgery Journal, 2023)
Patients with human immune-deficiency virus (HIV) have increased risk of developing hepatocellular carcinoma (HCC); this neoplasm apparently behaves more aggressively in this population, leading to worse outcomes. Questions remain regarding the best treatment of HCC in these patients, mainly related to the role of surgical resection. Some studies show that, after transplantation, this group of patients has an overall survival rate comparable to that of uninfected patients. This integrative review assesses and summarize the survival outcome of resection in the treatment of HIV-positive patients with HCC. Integrative review of articles published in English, in PubMed and Scielo databases until October 2021, using the terms: HIV, HCC, and resection. Four publications were analyzed in relation to their content and relevance to the research question. We identified 54 patients who underwent surgical resection, with great variability in overall survival between studies (median between 18 and 72 months); only one study demonstrated disease-free survival. There was also great variability in morbidity and mortality rates after the procedure. All studies were non-comparable. Data regarding the impact of surgical resection on survival in HIV-positive patients with HCC are scarce, and questions remain about the best treatment options with curative intent. Further studies on the topic are needed, given the practical implications for decision-making. Therefore, we suggest that the treatment of these patients should still be conducted similarly to that indicated by the main guidelines on the treatment of patients with HCC, without distinction to HIV serology.